Consideraciones ecológicas sobre la dieta, la reproducción y el parasitismo de Pseudopaludicola boliviana (Anura, Leptodactylidae) de Corrientes,Argentina - Duré Pitteri, Marta Inés (2004)
Ecological aspects of diet, reproduction and parasitism of Pseudopaludicola boliviana (Anura Leptodactylidae) from Corrientes, Argentina. The main objectives of this paper were to update the distribution range of Pseudopaludicola boliviana in Argentina, to determine its diet composition and the feeding patterns, to analyze some reproductive variables as mature ova count and diameter in relation to female snout vent length to describe the advertisement call from Argentinean populations, and to identify and localize its helminth parasites. Eleven prey types were identified; dipterans were more important both in number (23.53%) and in volume (41.30%); other important preys were collembolans, arachnids and coleopterans. The trophic niche width was 7.15 and the standardized trophic niche value was 0.61. Ovarian complement (number of mature ova for female) ranged from 50 to 319 (mean 175.3 ± 86. 2) while ovum diameter range from 0.2 to (mean 0.27 ± 0.062). The nuptial call is composed by five notes. The dominant frequency range from 3.488 to 5.927 kHz; emphasized frequency fluctuated between 4.942 and 5.224 kHz. A total of 10 helminth species (larvae and adults) were found in 54 (96%) infected frogs. Helminths were represented by Tematoda (7 species), Cestoda (1), Nematoda (1) and Acanthocephala (1).